TOLERANCE AS A RESULT OF CROSS-CULTURAL COMMUNICATION IN THE CONDITIONS OF GLOBALIZATION - Малинка, Ю. Г. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
In the article the questions of necessity of forming of tolerance modern society as internalss of person are examined in interests of successful conduct of cultural dialogue, cross-cultural collaboration and for prevention of cross-cultural conflicts, and also essence of concept is found out cross-cultural communication and tolerance.